THE HUMAN BETA-DEFENSIN-1 LEVEL FROM SMOKERS WITH CHRONIC PERIODONTITIS - Sulijaya, Benso; Masulili, Sri Lelyati C; Auerkari, Elza Ibrahim; Lessang, Robert; Soeroso, Yuniarti (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The role of human beta-defensin-1 (HBD-1) as an antimicrobial peptide in a smoker's periodontitis is still unclear, this study aimed to analyze the association of the levels of HBD-1 in smokers and non-smokers with chronic periodontitis. Methods: In total, 104 male subjects, 33-78 years old, were diagnosed to have chronic periodontitis in the Department of Periodontology, Oral Disease Special Clinic of the University of Indonesia. This cross-sectional study included clinical and laboratory examination. The data collected included those from anamnesis, clinical examination (oral hygiene index Siller, pocket depth, clinical attachment level), and smoking status. The samples were stored at âˆ’20Â°C until testing for HBD-1 level by enzyme-linked immunosorbent assay. Results: The median (min-max) HBD-1 level in the group of mild-moderate chronic periodontitis was 57.61 (0.87-343.58) pg/ml and in the group of severe periodontitis 15.27 (0.94-198.03) pg/ml (p=0.087). The median (min-max) HBD-1 level in non-smokers with chronic periodontitis was 27.82 (0.92-200.58) pg/ml, and in smokers 25.04 (0.87-343.58) pg/ml (p=0.457). Conclusion: There were no significant differences in the HBD-1 levels in subjects with chronic periodontitis regardless of the smoking status or severity of the disease. Keywords: Periodontitis, Î²-defensin, Smokers.